2020
DOI: 10.3390/jof6030157
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation in Ashbya gossypii

Abstract: Ashbya gossypii is a filamentous ascomycete belonging to the yeast family of Saccharomycetaceae. At the end of its growth phase Ashbya generates abundant amounts of riboflavin and spores that form within sporangia derived from fragmented cellular compartments of hyphae. The length of spores differs within species of the genus. Needle-shaped Ashbya spores aggregate via terminal filaments. A. gossypii is a homothallic fungus which may possess a and α mating types. However, the solo-MATa type strain is self-ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 101 publications
(142 reference statements)
0
5
0
Order By: Relevance
“…Next, we wanted to confirm the results obtained from the luciferase assay in modifying the expression of an A. gossypii endogenous gene. The MSN2 gene was selected because the alteration on its expression level triggers major changes in the sporulation ability of A. gossypii [28]. We previously observed that the overexpression of MSN2 nearly abolished the sporulation ability of A. gossypii, whereas the msn2∆ strain showed a significant increase in the sporulation capacity with respect to the wild-type strain (unpublished results).…”
Section: In Vivo Analysis Of New Promoter Sequencesmentioning
confidence: 96%
See 1 more Smart Citation
“…Next, we wanted to confirm the results obtained from the luciferase assay in modifying the expression of an A. gossypii endogenous gene. The MSN2 gene was selected because the alteration on its expression level triggers major changes in the sporulation ability of A. gossypii [28]. We previously observed that the overexpression of MSN2 nearly abolished the sporulation ability of A. gossypii, whereas the msn2∆ strain showed a significant increase in the sporulation capacity with respect to the wild-type strain (unpublished results).…”
Section: In Vivo Analysis Of New Promoter Sequencesmentioning
confidence: 96%
“…Moreover, it is also possible to further characterize the regulatory properties of each promoter by a genetic dissection of the promoter CIS-acting elements. A. gossypii, which is mainly considered a microbial factory, also represents an adequate model organism in cell biology studies regarding polarized growth and ploidy [28,29]; therefore, the availability of new molecular tools will strongly benefit A. gossypii research.…”
Section: Dual Luciferase Assay Of Selected Promoter Sequencesmentioning
confidence: 99%
“…Also salient from the literature is the long, thin ascus form in Metschnikowia and Eremothecium/Ashbya (Fig. 1 ; Lachance 2016 , Wendland 2020 ), which accommodates barbed, needle-like ascospores that may play a role in infection for some pathogens and dispersal in other species. As for the rest of Saccharomycotina , though the ascus structure is roughly globose, ascospore shape and ornamentation vary widely.…”
Section: Morphology Vegetative Growth and Sexmentioning
confidence: 99%
“…The filamentous ascomycete Ashbya gossypii is a pre-whole genome duplication fungus that belongs to the family of the yeasts Saccharomycetaceae and shares homologs of 95% of its genes with S. cerevisiae [ 15 ]. Previous studies have shown that the main regulators of sporulation in S. cerevisiae are also essential for sporulation in A. gossypii , including IME1 , IME2 , IME4 , KAR4 , NDT80 , and also the cAMP/Protein Kinase A pathway [ 16 , 17 , 18 ]. In S. cerevisiae , IME1 expression requires ScRim101, and sporulation is therefore dependent on alkaline pH [ 19 ].…”
Section: Introductionmentioning
confidence: 99%